The Psychometric Properties of the Norwegian version of Beck Depression Inventory 2. utgave (BDI II) - Siqveland, Johan; Kornør, Hege (PsykTestBarn, 2011)
Description: The Beck Depression Inventory II (BDI-II) is a 21-item multiple-choice self-report instrument developed to measure depression in persons aged 13 and above. The BDI-II was published in 1996, and is a revised version of the Beck Depression Inventory (BDI), published in 1961. The Norwegian version of the BDI-II was published in 2005; copyright holder Pearson Assessments. Each item in the BDI-II describes a symptom of depression. The participants are instructed to rate the severity of this symptom over the past two weeks on a 4-point Likert-type scale from 0 (absence of symptom) to 3 (severe manifestation of symptom). The BDI-II has a self-rating format and takes less than 30 minutes to complete. The scores are to be interpreted by a clinical psychologist or a medical doctor. Literature search: Our literature search identified 221 references; and 67 articles were read in full text. We included one article, one master thesis, and the manual in our evaluation. All included materials described the psychometric properties in adult populations. Psychometrics: Internal consistency reliability, test-retest reliability and external validity, as compared to other self-report forms, were all reported to be adequate. The agreement between the BDI-II score and the scores of various diagnostic interviews has not been investigated in any of the included studies. Conclusion: The Norwegian version of the BDI-II has demonstrated adequate psychometric properties in an adult population. Its psychometric properties in adolescent samples have not been documented. It has not been reported, whether the instrument is suitable for diagnosing depression severity. Thus, the Norwegian BDI-II provides no evidence for the clinical usefulness of the instrument for assessing or diagnosing depression, and scores need to be interpreted with caution.